On validation and typification of the name Festuca ×polovina (Poaceae): a correction and comments on indication of types of names of new taxa - Mosyakin, Sergei L.; Sokolova, Irina V.; Fedoronchuk, Mykola M. (Phytotaxa, 2018)
The controversial issue of valid publication and typification of the name Festuca ×polovina Bednarska (Poaceae) is discussed. It was assumed until recently that the name was published in 2009 invalidly because the author of the original description failed to cite the type (holotype) specimen. However, she indicated in the protologue that the holotype is deposited in the LWKS herbarium and mentioned the geographic origin of the taxon (Western Polissya of Ukraine). By this indication Bednarska fulfilled the requirements of Art. 40.6 and 40.7 of the ICN, and thus validly published the name. Fedoronchuk et al. (2010) cited the label of the supposed holotype in LWKS but did not mention the existence of three other duplicates in the same herbarium. Thus, Fedoronchuk et al. (2010) in fact cited the syntypes of the name. The specimen LWKS0030041 (cited as the “holotype” by Bednarska and Nachychko 2018) is designated here as the lectotype of the name F ×polovina. It is concluded that a proposal to amend the ICN is desirable for ensuring explicit citation and unambiguous indication of types (in particular, holotypes) for names of newly described taxa.